Central Asian Ismailis An Annotated Bibliography of Russian, Tajik and Other Sources - Dagiev, Dagikhudo (Ismaili Heritage, 2022)
The Shi'i Ismaili Muslims of Central Asia have a complex political history. This open access book is the first English-language study of the Ismaili Muslims in this region, based on analysis of the Russian, Soviet and post-Soviet scholarship about them. It sheds new light on their history and heritage, and also shows how the Ismailis of Central Asia have been understood and presented in the academic literature. Divided into three parts, the first covers the spread of the Ismaili da'wa (mission) throughout Central Asia - known as Khurasan - from the 3rd/9th century until modern times. This part examines the prominent poet da'i Nasir-i Khusraw, who played an instrumental role in the expansion and development of Ismailism in Badakhshan in the eleventh century and reveals the impact of his religio-philosophical legacy in the life of the contemporary community. The second part examines the initial interest in Ismaili Studies engendered by Russian imperial rule. It also shows how approaches to the study of Ismailism were affected by 70 years of Communist atheist rule and the demise of the Communist political and ideological system. The third part presents an annotated bibliography of books, articles, and published and unpublished materials, including documents and oral materials on the history, thought and practices of the Ismailis of Central Asia, most of which has not been hitherto easily accessible to Western scholarship. The comprehensive survey and rich bibliography aims to illuminate the history and historiography of the Ismailis in Central Asia and facilitate further study on the subject by experts around the world.